Experiences and practices of traditional healers on snakebite treatment and prevention in rural Malawi. - Moses Banda Aron; Manuel Mulwafu; Bright Mailosi; Benno Kreuels; Luckson Dullie; Chiyembekezo Kachimanga; Jörg Blessmann; Enoch Ndarama; Clara Sambani; Fabien Munyaneza; Anat Rosenthal (Public Library of Science (PLoS), 2023)
Snakebite envenoming remains a public health threat in many tropical countries including Malawi. Traditional healers (THs) have been consulted by victims of snakebites as primary caregivers for millennia. There are no studies in Malawi to understand this phenomenon, therefore, our study aimed to explore the experiences and practices of THs regarding snakebite treatment and prevention in rural Malawi. Between August and September 2022, we conducted semi-structured interviews with 16 THs who were purposefully selected from various locations across Neno District, Malawi. We analysed the interview data using Dedoose software, where we generated codes and grouped them into themes. Out of the 16 THs interviewed, 68.8% (n = 11) were male, and 43.8% were aged between 40 and 60 years. Our study identified five themes: THs' knowledge of snakes and treatment, the continuum of care they provide, payment procedures, snakebite prevention, and their relationship with health facilities. They claimed a good understanding of the snakes in their area, including the seasons with more snakebites, and were confident in their ability to provide treatment, however, this was not scientifically proven. They offered a comprehensive care package, including diagnosis, first aid, main treatment, and follow-up care to monitor the victim's condition and adjust treatment as needed. THs provide free treatment for snakebites or use a "pay later" model of service delivery. All THs claimed a "vaccine" for snakebites that could prevent bites or neutralize the venom. However, no formal relationship existed between THs and Health Care Workers (HCWs). We recommend collaboration between HCWs and THs, establishing clear referral pathways for snakebite victims and educating THs on identifying danger signs requiring prompt referral to healthcare facilities.